2012
DOI: 10.1111/j.1439-0272.2012.01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Aminoguanidine prevents testicular damage-induced-2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) in male rats

Abstract: Summary In this study, it was aimed to determinate protective effects of aminoguanidine (AG) against reproductive toxicity caused by 2,3,7,8‐tetrachlorodibenzo‐p‐dioxin (TCDD), an environmental contaminant. Thirty‐two rats were equally divided into four groups; the first group was kept as control and given corn oil as carrier. In second and third groups, TCDD and AG were orally administered at the dose of 2 μg kg−1 per week and 100 mg kg−1 per day for 45 days, respectively. In fourth group, TCDD and AG were gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…Our findings are in agreement with animal data showing TCDD inhibition of testicular development and function during critical periods of reproductive-tract development, including fetal, neonatal ( Arima et al 2009 ; Faqi et al 1998 ), pubertal ( el-Sabeawy et al 1998 ), and adult stages ( Oguz et al 2013 ; Sönmez et al 2011 ). Moreover, childhood exposures to dioxins, furans, and PCBs have been shown to adversely affect other key maturational processes, such as somatic growth and pubertal timing in our cohort ( Burns et al 2011 , 2016 ; Korrick et al 2011 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in agreement with animal data showing TCDD inhibition of testicular development and function during critical periods of reproductive-tract development, including fetal, neonatal ( Arima et al 2009 ; Faqi et al 1998 ), pubertal ( el-Sabeawy et al 1998 ), and adult stages ( Oguz et al 2013 ; Sönmez et al 2011 ). Moreover, childhood exposures to dioxins, furans, and PCBs have been shown to adversely affect other key maturational processes, such as somatic growth and pubertal timing in our cohort ( Burns et al 2011 , 2016 ; Korrick et al 2011 ).…”
Section: Discussionsupporting
confidence: 93%
“…In this sense, Balercia et al [43] found that asthenozospermic men show greater levels of NO • than normozoospermic men and that the concentration of this gasotransmitter were negatively correlated with the sperm motility. In this way, our findings indicate that aminoguanidine can be employed for protecting against the effects of oxidative stress in sperm cells, which is consistent with the findings in other cells and tissues (lung: [44]; bladder: [45]; kidney: [46]; testis: [29]). Similarly, Abbasi et al [30,31] and Alizadeh et al [32,33] found that the in vivo administration of aminoguanidine improves the sperm concentration, motility, viability, normal morphology, mitochondrial membrane potential, and DNA integrity in varicocelized rats where the upregulation of the iNOS isoform may lead to high levels of ROS in the semen.…”
Section: Discussionsupporting
confidence: 89%
“…In a recent study conducted by our research group [28], we found that aminoguanidine improves some sperm kinetic parameters during boar semen storage at 17 °C. Moreover, aminoguanidine protects against the negative effects of oxidative stress induced by environmental pollutants [29] and pathological conditions, such as varicocele [30,31,32,33]. Nonetheless, the in vitro effects of aminoguanidine on sperm cells under induced oxidative stress are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Oguz et al . () declared that AG treatment reversed 2,3,7,8‐tetrachlorodibenzo‐p‐dioxin (TCDD)‐induced testicular damage in rats. The protective effect of AG has been thought to be related to its effects on reduction in free‐radical production and amelioration in antioxidant contents in the renal and testis tissue.…”
Section: Introductionmentioning
confidence: 99%